1976
DOI: 10.1111/j.1365-2133.1976.tb05167.x
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of methods of treating viral warts by comparative treatment trials based on a standard design

Abstract: A series of eleven comparative wart treatment trials undertaken between 1969 and 1975 and involving 1802 patients is described. A method of coding provided groups of patients matched for age, type, number and duration of warts, within which treatments could be randomized. The variation in response to treatment was shown to be influenced significantly by these factors and the level of cure to depend on the proportions of the various response groups within the population under consideration. These proportions we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
130
2
8

Year Published

1977
1977
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(153 citation statements)
references
References 6 publications
7
130
2
8
Order By: Relevance
“…The cure rate for the two-week interval treatment group and the three-week interval treatment group was similar. Considering the cure rate, our results were similar to those of Bunney et al 20 , which showed the cure rate for the two-week interval patients as 78% and the cure rate for the three-week interval patients as 75%. They suggest that the interval between treatments should not be longer than three weeks, because four weeks intervals showed a much lower cure rate of 40%.…”
Section: Discussionsupporting
confidence: 80%
“…The cure rate for the two-week interval treatment group and the three-week interval treatment group was similar. Considering the cure rate, our results were similar to those of Bunney et al 20 , which showed the cure rate for the two-week interval patients as 78% and the cure rate for the three-week interval patients as 75%. They suggest that the interval between treatments should not be longer than three weeks, because four weeks intervals showed a much lower cure rate of 40%.…”
Section: Discussionsupporting
confidence: 80%
“…trained all participating family physicians and assistants working in their practices in the three 13-week treatment protocols, which were designed to reflect best practice. 10,24 Training consisted of a one-hour interactive practical session, during which all tools and techniques were demonstrated; real warts were not used in the demonstrations.…”
Section: Treatment Protocolsmentioning
confidence: 99%
“…All treatment modalities are associated with substantial pain, tissue destruction, and frequent recurrences, however these procedures are not well tolerated by children owing to pain and fear. 4,5 Potassium hydroxide (KOH) is known to penetrate deeply and destroy the skin because it dissolves keratin. 6 Five percentage of KOH solution has been prescribed for molluscum, to be applied at home and has added advantage of being relatively painless.…”
Section: Introductionmentioning
confidence: 99%